inggris An Analysis of Illocutionary Acts in The Lyrics of The Songs 'Kun Rahma' and 'Muhammad (PBUH) Waheshna' - Gazali, Erfan; Alwani, Tamim (Diwan : Jurnal Bahasa dan Sastra Arab, 2024)
تهدف هذه الدراسة إلى توصيف أشكال ووظائف الأفعال الكلامية الإنجازية في كلمات أغنيتي ”كن رحمة“ و”محمد (صلى الله عليه وسلم) وحشنا“. قام أحمد اليافعي بصياغة أغنية ” كن رحمة“، وقام ماهر زين بتلحينها ونشرها عام 2007. وتتضمن الأغنية قيمًا اجتماعية عن حسن معاملة الأطفال الصغار، خاصةً أولئك الذين يعانون من مشاكل في حياتهم. صاغ محمود فاروق كلمات أغنية ”محمد (صلى الله عليه وسلم) واحشنا“ التي أشاعها ماهر زين وطُرحت عام 2003، بينما لحن محمود فاروق موسيقاها. تعبر كلمات الأغنية عن فيض من العاطفة، وتحديدًا الشوق إلى النبي محمد (صلى الله عليه وسلم). بالإضافة إلى أن ماهر زين وحده من قام بتلحين كلمات الأغنيتين. توظف هذه الدراسة منهجية البحث الوصفي النوعي باستخدام تقنية مراجعة الأدبيات. ويوظف جمع البيانات في هذا البحث منهج الاستماع. والتقنية الأساسية المستخدمة في هذا المنهج هي تقنية التنصت، بينما التقنية الأكثر تطوراً المستخدمة هي تقنية تدوين الملاحظات. استخدمت الدراسة التقنية القابلة للمقارنة لتحليل البيانات. ويستخدم في تصنيف العناصر الأساسية منهجية عملية، كما أن القدرة على ترتيبها تلتزم أيضًا بهذا المنهج العملي. وتشير النتائج إلى أن هناك نوعين من الأفعال الإنجازية في 26 كلمة من كلمات أغنية ”كن رحمة“، في حين تم تحديد ثلاثة أنواع من الأفعال الإنجازية في 17 كلمة من كلمات أغنية ”محمد (صلى الله عليه وسلم) وحشنا“. وبالإضافة إلى ذلك، تحتوي كلمات أغنية ” كن رحمة“ على أربعة أنواع من الأفعال الإنجازية المستمدة من نوعين من الأفعال الإنجازية. وبالمثل، تشتمل كلمات أغنية ”محمد (صلى الله عليه وسلم) واحشنا“ على خمس وظائف من الأفعال الإلقائية، وهي مشتقة من ثلاثة أنواع من الأفعال الإنجازية. Abstract This study aims to analyze the forms and functions of illocutionary speech acts in the lyrics of the songs "Kun Rahma" and "Muhammad (Pbuh) Waheshna." Ahmed Al-Yafie penned the song 'Kun Rahma', Maher Zain popularized it, and it was released in 2007. The song conveys social values, particularly in how to treat young children, especially those who have those in distressing situations. Mahmoud Farouk written the lyrics of 'Muhammad (Pbuh) Waheshna', which Maher Zain popularized and released in 2003, while Mahmoud Farouk composed the music. The song's lyrics express deep emotions, specifically longing for the Prophet Muhammad (Pbuh). In addition, Maher Zain alone popularised both song lyrics. This study employs a descriptive qualitative research methodology, utilising a literature review technique. Data collection in this research is conducted using a listening approach. The tapping technique as the primary method, while the a supplementary approach is the note-taking technique. The study used the comparable technique for data analysis. The categorization of essential elements follows a practical methodology, and the ability to arrange them also adheres to this practical approach. The findings indicate that there are two types of illocutionary acts seen in 26 lyrics of the song 'Kun Rahma', whereas three types of illocutionary acts are identified in 17 lyrics of the song 'Muhammad (Pbuh) Waheshna'. In addition, the lyrics of the song 'Kun Rahma' contain four functions of illocutionary activities, which are derived from two types of illocutionary acts. Similarly, the lyrics of the song 'Muhammad (Pbuh) Waheshna' encompass five functions of illocutionary acts, originating from three forms of illocutionary acts.